Toward Assessing Farm-Based Anaerobic Digestate Public Health Risks: Comparative Investigation With Slurry, Effect of Pasteurization Treatments, and Use of Miniature Bioreactors as Proxies for Pathogen Spiking Trials - Nolan, Stephen; Waters, Nicholas R.; Brennan, Fiona; Auer, Agathe; Fenton, Owen; Richards, Karl; Bolton, Declan J.; Pritchard, Leighton; O'Flaherty, Vincent; Abram, Florence (Frontiers in Sustainable Food Systems, 2018)
Manure and slurry may contain a range of bacterial, viral, and parasitic pathogens and land application of these organic fertilizers typically occurs without prior treatment. In-situ treatment through farm-based anaerobic digestion (AD) of such organic fertilizers co-digested with food-production wastes is multi-beneficial due to energy recovery, increased farm incomes and noxious gas reduction. Before risk assessment can be carried out at field scale an investigation of the fate of relevant target pathogens during the actual AD process must be undertaken, requiring the development of practical test systems for evaluation of pathogen survival. The present study examines miniature (50 mL) and laboratory (10 L) scale AD systems. Treatments included slurry co-digested with fats, oils, and grease (FOG) under typical operating and pasteurization conditions used in farm-based AD, in batch-fed miniature and laboratory mesophilic (37°C) continuously stirred tank reactors. Biogas production, pH, chemical oxygen demand, volatile solids, and ammonia concentration were measured throughout the trial, as were fecal indicator bacteria (FIB) i.e., total coliforms, Escherichia coli, and Enterococcus species. The miniature and laboratory bioreactors performed similarly in terms of physicochemical parameters and FIB die-off. In the absence of pasteurization, after 28 days, enterococci numbers were below the <1,000 cfu g−1 threshold required for land application, while E. coli was no longer detectable in the digestate. For comparison, FIB survival in slurry was examined and after 60 days of storage, none of the FIB tested was <1,000 cfu g−1, suggesting that slurry would not be considered safe for land application if FIB thresholds required for AD digestate were to be applied. Taken together we demonstrate that (i) miniature-scale bioreactors are valid proxies of farm-based AD to carry out targeted pathogen survival studies and (ii) in situ AD treatment of slurry prior to land application reduces the level of FIB, independently of pasteurization, which in turn might be indicative of a decreased potential pathogen load to the environment and associated public health risks.